2022
DOI: 10.3390/nano12091393
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Strong Interlayer Couplings in WS2/MoS2 Heterostructures via Low-Frequency Raman Spectroscopy

Abstract: Van der Waals (vdW) heterostructures based on two-dimensional (2D) transition metal dichalcogenides (TMDCs), particularly WS2/MoS2 heterostructures with type-II band alignments, are considered as ideal candidates for future functional optoelectronic applications owing to their efficient exciton dissociation and fast charge transfers. These physical properties of vdW heterostructures are mainly influenced by the interlayer coupling occurring at the interface. However, a comprehensive understanding of the interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…According to the procedure reported in previous work, multilayer WS 2 and MoS 2 flakes were mechanically exfoliated on SiO 2 /Si (270 nm) substrates and transferred to form vdWSs by the dry method with polymer stamps. 15 Raman spectra obtained with 532 nm excitation show the E 1 2g and A 1g peaks of WS 2 and MoS 2 , located at 354 cm −1 ,421.5 cm −1 and 384 cm −1 , 408.5 cm −1 respectively, 16 consistent with the multilayer structure (see ESI, Fig. S1 †).…”
Section: Resultssupporting
confidence: 56%
“…According to the procedure reported in previous work, multilayer WS 2 and MoS 2 flakes were mechanically exfoliated on SiO 2 /Si (270 nm) substrates and transferred to form vdWSs by the dry method with polymer stamps. 15 Raman spectra obtained with 532 nm excitation show the E 1 2g and A 1g peaks of WS 2 and MoS 2 , located at 354 cm −1 ,421.5 cm −1 and 384 cm −1 , 408.5 cm −1 respectively, 16 consistent with the multilayer structure (see ESI, Fig. S1 †).…”
Section: Resultssupporting
confidence: 56%
“…Additionally, XPS analysis indicated that the few-layer WS x , after selenization at 600 °C for 2400 s, showed an almost stoichiometric composition of WS 0.3 Se 1.7 (Figure S1), while the Stokes and anti-Stokes Raman spectra indicated 5–6 (few-layer) stacked layers for both WS 0.3 Se 1.7 and WS 2 (Figures S2 and S3). In addition, the XRD pattern of WS 0.3 Se 1.7 shows peaks at 14.20° and 61.82° in agreement with the (002) and (112) diffraction planes with narrow full width at half-maximum (FWHM ∼ 0.2°) for the WSe 2 and WS 2 , respectively, whereas the hexagonal structure film formation indicated by the appeared peak of (002) (Figure S4). Figure b shows the schematic of the FET device structure and PL map image of the plasma-jet exposed area between the S/D electrodes (with a jet spot area of ∼8.0 μm 2 ).…”
Section: Resultssupporting
confidence: 55%
“…Two major bands of A 1g and E 2g are observed that are traditionally observed in WS 2 . 38 Fig. 2a represent the SEM image of NF sputtered with pure WS 2 .…”
Section: Resultsmentioning
confidence: 99%